PENGARUH KENERJA PELAYANAN TENAGA MEDIS TERHADAP KEPUASAN PASIEN BPJS DI PUSKESMAS EYAT MAYANG KABUPATEN LOMBOK BARAT - Hilda Sapitri; Muhammad Habibullah Aminy; Slamet Mardiyanto Rahayu; Lale Ajeng Khalifatun Wardani; Muhammad Aditya Rachman; Wahyu Aprilyaningsih (Nusadaya Journal of Multidiciplinary Studies, 2025)
The significance value of the t-test is 0.001, which is smaller than the critical limit of 0.05, so H₀ is rejected and H₁ is accepted. The regression coefficient value is 0.386, indicating that improving the quality of service performance will increase BPJS patient satisfaction. The R Square value is 0.215, which means that 21.5% of the variation in BPJS patient satisfaction can be explained by service performance factors, while the rest is explained by other factors. Although service performance has a significant influence on patient satisfaction, the R Square value of 21.5% indicates that there is still 78.5% of the variation in patient satisfaction that is influenced by other factors outside the performance of medical personnel services. These factors can include the condition of the facility, the attitude of administrative staff, ease of access to services, waiting time, and psychological and social aspects of patients.